Complexity analysis of monthly precipitation in the state of Pernambuco using Sample Entropy (Research, Society and Development, 2020)
Rainfall is one of the phases of the hydrological cycle responsible for the return of the condensed water from the atmosphere to the Earth's surface. It is a natural process of utmost importance for ecosystem functioning because it regulates water availability for various uses and environmental services. The present work aims to assess the rainfall variability in Pernambuco, Brazil, using monthly precipitation data for the period from 1950 to 2012, collected from the Meteorological Laboratory of Pernambuco State (LAMEP), division of the Technological Institute of Pernambuco (ITEP). Data were analyzed using the Sample Entropy method (SampEn) developed to quantify the complexity of nonlinear time series, and interpolated by Inverse Distance Weighting (IDW) method, providing an estimate of the complexity of the rainfall in the state of Pernambuco. The results show that for all regions of Pernambuco, entropy values of monthly rainfall series are classified from moderate to low, indicating the feasibility of modeling of precipitation dynamics on a monthly scale.